Identification, Biology, and Control of Small-Leaf Spiderwort (Tradescantia fluminensis): A Widely Introduced Invasive Plant - Jason C. Seitz; Mark W. Clark (EDIS)
Tradescantia fluminensis (small-leaf spiderwort) is a perennial subsucculent herb native to tropical and subtropical regions of Brazil and Argentina. The species has been introduced to the United States and countries in many parts of the world where it is often considered invasive. This 7-page fact sheet describes the small-leaf spiderwort, its taxonomy, geographical distribution, biology and ecology, reproduction and colonization, its impact as a weed in the southeastern United States, and ways of managing the spread of small-leaf spiderwort. Written by Jason C. Setiz and Mark W. Clark, and published by the Department of Soil and Water Science, January 2016.